Legal Analysis of Land Rights Transfer Mechanisms and Their Implications for Land Ownership in Indonesia - Aslan Noor; Aliya Aisyah Aminy; Aprilia Salsabila; Jessen Rivandi; Orindianisa Hanifah Runandanatadila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The transfer of land rights is a legal process that determines the validity of changes in the identity of rights holders, the evidentiary force of legal documents, and the certainty of land ownership. Although it is regulated under Law Number 5 of 1960 concerning the Basic Regulations on Agrarian Principles and Government Regulation Number 24 of 1997 concerning Land Registration, certain provisions of which were amended through Government Regulation Number 18 of 2021, its implementation continues to encounter problems involving privately executed land sale and purchase transactions, document forgery, transfers conducted by unauthorized parties, multiple certificates over the same parcel of land, and inconsistencies in physical and juridical data. This research aims to analyze the juridical characteristics of land-right transfers; the construction of positive law, legal doctrine, and judicial decisions in determining their validity; and their implications for justice, utility, and legal certainty. This study employs normative legal research using statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively and prescriptively using grammatical, systematic, and teleological interpretation. The findings demonstrate that the validity of a transfer of land rights is determined by the continuity of material, formal, and administrative validity. Transfers arising from legal acts generally require evidence prepared by an authorized official and registration, whereas transfers through inheritance are based on different evidentiary requirements. A land title certificate constitutes strong evidence but does not possess absolute evidentiary force because it may be annulled when its issuance is based on defects of authority, procedural defects, forgery, or inaccurate data. This research finds that certainty of land ownership should be directed toward the concept of verified certainty, namely certainty based not only on the existence of a certificate but also on the accuracy of the subject, object, underlying title, authority, and history of transfers. Strengthened data validation, PPAT due diligence, integrated land administration, and measurable correction mechanisms are required to achieve fair and effective legal protection.